AKUNTANSI SOSIAL BENTUK KEPEDULIAN PERUSAHAAN TERHADAP LINGKUNGAN - Luhgiatno . (STIE Pelita Nusantara Semarang, 2007)
Upon, the corporation focus in a bussiness was to get financial adventages only. The bussinessman have not been demanded to give attention to the effect of their corporations services to the steak holder (either directly nor indirectly). Now, the corporations services cannot be run any more without regarding the internal surrounding (employees, investors) or external surrounding (public and environment). To show the attention process with the recycled residue which is not polluse the environment and to many ways to conserve the environment.The corporations attentions to the environment must be in creased in reformation era which is showed by the transparancy increase. The corporation which do not have the social and environment attention will get many obstacles such as getting public go strike, even the corporation will be stopped producting by the authority.